ANALYSIS OF STABILITY AND SAFETY OF TECHNICAL SYSTEMS THAT GOVERN OPERATOR - Draganov, B. (Енергетика і автоматика, 2016)
A method for determining the knowledge and skill of the operator of the technical system. The analysis is based on an information block and representation in the form of the corresponding matrices.